Immersive storytelling experiences: a design methodology - Polydorou, Doros (Digital creativity (Exeter), 2024)
This paper synthesizes the findings from The Last Play, The Fall of R'Thea and Sticklebacks, three immersive storytelling experiences developed by the author and his collaborators over a span of four years. We define 'immersive storytelling' as a time-limited, location-based experience that invites audiences into a fragmented narrative across multiple mediums. Engaging various senses and requiring active participation, the experience adapts to individual choices and uses technology as a tool to expand the narrative spaces. Through this paper, we provide insights into our creative approaches, methodologies, and the lessons learned during the development and production phases and propose an immersive design methodology aimed at guiding future research and practice in crafting immersive experiences.